Answer:
y=-x+2
Step-by-step explanation:
The slope-intercept form is y=mx+b where m is the slope and b is the y-intercept.
From the graph, we can see that the y-intercept is at (0,2) so the equation becomes y=mx+2.
Other points on the graph include (1,1) and (2,0). Plugging (1,1) into the slope-intercept equation, we get 1=(m)1+2. Solving this will give us m=-1.
We can confirm this by plugging m=-1 into the equation along with the point (2,0); 0=(-1*2)+2. It checks out!
So our final equation in slope-intercept form will be y=-x+2
Answer:
-2x^2 +16x -8
Step-by-step explanation:
Oh s-
Like terms i guess Same variable you can substract. Remember you only substract from 1 number not from all.
-2x^2 stays the same as there is no like term
9x - (-7x)
-2 - (6)
-2x^2 + 9x+ 7x -2-6
-2x^2 +16x -8
Answer:
4z -6< - 10= Z= < -1
5z - 3 >7= Z=< 2
Step-by-step explanation:
The answer is 2.34 x 10-11 g